K3 IMPLEMENTATION AND PSYCHOSOCIAL WORKING AREA EFFECT AT SP II FACTORY (Slab Steel Plant) P.T. KS MELTING UNIT - Aliva Kemala (Universitas Gunadarma, 2008)
The implementation of healthy and safety work is playing a significant role in creating working area securely, healty and safely. But the programe doesn’t have guarantee that the job and condition working area will alway be secure, healty and safe. Healt and safety work constitute one of the efforts for reducing the possibility of work accident risk, work ilness and polution area. This research use method qualitative case study. Participant of this studiy are two official employees at SSP II factory PT. KS Melting Unit. The collecting data technique for this study are observation and interview. The application of the program at factory SSP II PT. KS Unit Melting is already good. On the other hand, the working condition area in factory SSP II PT. KS Unit Melting has psychososial effects and influences employees’ emotion such as higher voice intonation as if shouting or being angry with another person, easy to get annoyed or feeling unhappy, and also has sleeping problems because of the noisy working condition. The other effects are hot temperature and dust that make the employees easy to feel tired quickly.Keywords : Healthy and safety work, psychososial working area effect